Family Ownership and Political Costs on Manufacturing Company Performance in Indonesia 2016-2020 - Akbar Evandio; Juniati Gunawan; Idrianita Anis (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The issue of family proprietorship and political expenses on the presentation of assembling organizations is a fascinating conversation to study. This sort of study is quantitative exploration. The independent factors in this study incorporate family proprietorship and political expenses, while the dependent variable is organization performance. The research population is manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The results show that family ownership has a positive influence on company performance and political costs have a negative effect on company performance. Simultaneously, family ownership and political costs have a significant affect company performance with the commitment of R2 worth of 22.10%.